Effect of Sintering Temperature and AR Glass Addition towards Physical Properties of Porcelain Ceramic for Sewer Pipes Application - Ikhmal, Muhammad; Ahmad, Sufizar; Taib, Hariati; Chen, Tan Chee (International Journal of Integrated Engineering, 2018)
The current work is aimed to investigate significant phase changes at certain sintering temperature in manufacturing ceramic pipes for sewer application. The use of porcelain ceramic reinforced with milled Alkali Resistant (AR) fiberglass (3 wt%, 6 wt%, 9 wt% and 12 wt%) was determined in this study. Both of raw materials were turned into powder to conduct thermal analysis and produce a compact sample. The powder was compacted by uniaxial pressing technique to examine the analysis of volume shrinkage. Volume shrinkage was done by measuring the dimension of green body and sintered sample (900°C, 1000°C 1100°C and 1200°C). The image of microstructural morphology was observed by Scanning Electron Microscope. TG graph indicates large amount of mass loss found to be 75% between 450°C to 800°C for porcelain and all mixtures. While DT graph reveals the endothermic shift produce at 250°C. The maximum volume shrinkage was obtained at 1200°C which is 31.7% with 3 wt% AR glass addition. The microstructural image proved the correlation to volume shrinkage. The presence of glassy phase demonstrates the formation of eutectic where shrinking particle takes place to construct dense sample.